Role of EUS-FNA for gallbladder mass lesions with biliary obstruction: a large single-center experience - Singla, Vikas; Agarwal, Rachit; Anikhindi, Shrihari Anil; Puri, Pankaj; Kumar, Mandhir; Ranjan, Piyush; Kumar, Ashish; Sharma, Praveen; Bansal, Naresh; Bakshi, Pooja; Verma, Kusum; Arora, Anil (Endoscopy International Open, 2019)
Background and study aims Although endoscopic ultrasound (EUS)-guided fine-needle aspiration (EUS-FNA) is an established modality for pathological sampling of pancreatic and biliary lesions, limited data are available on the diagnostic value of EUS-FNA for evaluation of gallbladder mass lesions, a common cause of obstructive jaundice. We aimed to evaluate the usefulness of EUS-FNA for diagnosis of gallbladder mass lesions presenting with biliary obstruction.Patients and methods This study was a retrospective analysis of data from patients who had undergone EUS-FNA for gallbladder mass lesions. FNA was performed on either a gallbladder mass, metastatic node or liver lesions. Outcome measures were diagnostic yield of EUS FNA and adverse events.Results From April 2011 to August 2018, 101 patients with gallbladder mass lesions with biliary obstruction underwent EUS-FNA. The final diagnosis was malignancy in 98, benign disease in one, and two patients were lost to follow-up. EUS-FNA confirmed the diagnosis in 89 of 98 patients with malignancy (sensitivity 90.81 %); was false negative in nine of 98 cases with malignancy; and was truly negative in the solitary patient with benign disease (specificity 100 %). Positive predictive value, negative predictive value (NPV), and accuracy were 100 %, 10 %, and 90.90 %, respectively. Two patients had self-limiting pain.Conclusion EUS-FNA is a sensitive tool for evaluation of gallbladder mass lesions presenting with obstructive jaundice. However, because of low NPV, lesions in which FNA is negative should be further evaluated.